The Jordan Stillbirth and Neonatal Mortality Surveillance (JSANDS) System: Evaluation Study - Yousef Khader; Mohammad Alyahya; Ziad El-Khatib; Anwar Batieha; Nihaya Al-Sheyab; Khulood Shattnawi (JMIR Publications, 2021)
BackgroundThe Jordan Stillbirth and Neonatal Mortality Surveillance (JSANDS) is an electronic surveillance system that automatically transfers the data on births, stillbirths, and neonatal deaths to the concerned authorities in the Ministry of Health. JSANDS was implemented and tested in 5 maternity hospitals during the period spanning May 2019 through December 2020. ObjectiveThis study aimed to evaluate the usefulness and performance of JSANDS to register births, stillbirths, and neonatal deaths, and determine their causes. Specifically, this study examined the JSANDS attributes of acceptability, simplicity, flexibility, stability, representativeness, sustainability, penetration, data quality, sensitivity, and adoption. MethodsAn evaluation study was conducted after 18 months of the JSANDS implementation using the Updated Guidelines for Evaluating Public Health Surveillance Systems. The evaluation focused on how well the system operated to meet its purpose and objectives. The indicators assessing the system attributes were scored on a Likert scale. Each indicator and overall attribute percentage score was represented as score rank and interpreted as excellent (score ≥80%), good (score ≥60 and <80%), average (score ≥40 and <60%), and poor (score <40%). ResultsA total of 270 health care professionals participated in this study and evaluated the system performance. The system users rated the usefulness of JSANDS as excellent (percentage score=85.6%). The overall acceptability (percentage score=82.3%), flexibility (percentage score=80.2%), stability (percentage score=80.0%), and representativeness (percentage score=86.6%) were also rated excellent. The overall simplicity was scored good (percentage score=75.4%). All participants were trained on JSANDS and used it in the past 12 months. Of the 270 respondents, 219 (86.2%) reported that they intend to continue using the JSANDS system to register neonatal deaths and stillbirths in the future. All variables in JSANDS had complete data with no missing values. ConclusionsThe performance of JSANDS in registering all stillbirths and neonatal deaths as well as their causes was excellent. Almost all attributes and indicators of JSANDS functionality were rated excellent. JSANDS can be scaled up to cover all maternity hospitals in Jordan. The potential for scaling up the system is very high for many reasons, including its usefulness, simplified stillbirth and neonatal death review tools, and ease of the reporting process.